Latin American Childhoods: Racist Civilisation and Social Cleansing - Liebel, Manfred (Sociedad e Infancias, 2017)
In the colonization of the subcontinent that we now call Latin America, similar to that of other continents, the European conquerors considered the native peoples as childish. Childlike analogies attributed to the colonized peoples a limited intellect, which made it possible to justify colonization as a civilizing mission and discriminatory and racist treatment of the children of these peoples, and those resulting from sexual relations between conquerors and indigenous and afro-descendant women. In this essay, the author presents different practices but their origins are similar: first, the racist arbitrariness given to so-called “illegitimate” or “irregular” children; second, the treatment of indigenous and afro-descendant children with the end of “civilizing” them; and third, the persecution and “social cleansing” against children who do not meet the pre-dominant notions of a socially accepted childhood. These practices are based on the racist concepts of colonial rulers and have repercussions on Latin American societies to this day.